An Empirical Study on Continuation Writing in Senior High School under the Assessment and Feedback of ChatGPT - Wang, Jingjing (Journal of Theory and Practice of Contemporary Education, 2024)
With the integration of generative AI in English education, its potential application in English writing assessment could have a transformative impact on high school English instruction. This study employs both quantitative and qualitative research methods, using pre-tests and post-tests, questionnaires and interviews to investigate the effects of ChatGPT and teacher feedback on high school students’ writing proficiency and motivation in English continuation writing tasks within a foreign language teaching context. The experiment showed that after two months of instruction with feedback from both ChatGPT and teachers, writing scores of both groups improved significantly. However, the performance of the experimental group did not significantly exceed that of the control group. Most students appreciated the feedback from ChatGPT, yet remained neutral about its potential to replace teacher feedback. Effectively combining intelligent feedback with teacher feedback, to leverage their strengths, can enhance teaching and assessment efficiency, ultimately improving students’ proficiency and interest in English writing.